Histopathology and transmission electron microscopy of the bursa of fabricius following ibd vaccination and ibd virus challenge in chickens - Luengo, Amelia; Butcher, Gary; Kozuka, Yoshimichi; Miles, Richard (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
Two experiments were conducted in order to determine comparative severity of gross, histopathologic, and ultrastructural lesions among six lines and five cross-mating of chickens to infectious bursal disease virus (IBDV). In these experiments, 1,260 lines of chickens and 420 cross-mating of chickens and 200 Specific-Pathogen-Free (SPF) chickens were used. In the experiment one, chickens were vaccinated at 4 weeks of age by the oral route with a commercial intermediate live IBD vaccine. Samples of bursa of Fabricius at 4,8, and 11 weeks (wk) of age, were collected and fixed in 10% buffer formaldehyde for histophatologic study, or in a mixture of 2.5% glutaraldehyde, 1% paraformaldehyde, 0.05 M calcium chloride in 0.2 M sodium cacodylate-HCl buffer pH 7.2, 350 mOsm, for TEM study. Tissue samples were subsequently post-fixed in osmium and dehydrated through graded alcohol then embedded in epoxy resin. Ultrathin sections were doubly stained in uranyl acetate and lead citrate and observed using Hitachi H-7100 TEM. Seven wk after vaccination, histopathologic study showed bursae atrophy and reduced bursa:body weight (B:BW) ratios, which may imply a concurrent potential decrease in immune competence of chickens following IBD vaccination. Transmission electron microscopy study demonstrated IBD virions in cytoplasm of lymphocytes in bursa tissues from vaccinated lines and cross-mating of chickens and SPF chickens. In experiment two, 1,480 lines and 520 cross-mating of chickens and 210 SPF chickens were challenged with IBD standard challenge virus, at 4 weeks of age by the eye drop route. The mortality after challenge was 4% in lines and cross-mating chickens and 29% in SPF chickens. The histopatholgic and ultrastructural lesions were studied at 3, 7, and 24 days after challenge. The lesions were follicular lymphoid necrosis, depletion, and acute inflammation with edema, hemorrhage, and heterophils infiltration through the observation period of 24 days. The severity of bursal lesions were greater and more persistent in SPF chickens than in the lines and cross-mating chickens. Bursa samples from infected chicken were macerated and centrifuged, and the supernatants were directly applied to membrane supported grids for negative staining with 1% neutralized PTA. Ultrathin sections of bursal tissues from infected chickens revealed viral inclusions in the cytoplasm of lymphocytes and macrophages. In conclusion, these findings suggest that lines and cross-mating chickens had greater immune resistance to IBDV challenge than SPF chickens, which is possibly due to genetic factors.